REXUS-4 - Vehicle and Experiments, Outlook on the REXUS/BEXUS Student Programme - Stamminger, Andreas; Czech, Manuel; Griebel, Hannes; Hörschgen, Marcus; Persson, Olle; Pinzer, Markus; Riesselmann, Jens (2009)
On the 22nd of October 2008, EuroLaunch launched the REXUS-4 rocket at Esrange in Northern Sweden. EuroLaunch is a joint venture of the DLR Mobile Rocket Base and the SSC Esrange Space Center. REXUS-4 was a two-stage unguided solid propellant sounding rocket. The vehicle consisted of a Nike motor as 1st stage, an Improved Orion motor as 2nd stage, a motor adapter, a recovery system, a service system, two experiment modules, and a nosecone. The REXUS-4 payload was comprised of five technological experiments from German and Swedish Universities. The rocket was spin-stabilized during the ascent. After the burn-out of the 2nd stage a yoyo system de-spun the rocket to a rate of only a few degrees per second. At an altitude of 71 km the nosecone was jettisoned. The payload reached its apogee at 175 km. The REXUS-4 mission was also the maiden flight of a newly developed rocket service system. After this successful demonstration, it has been implemented into the REXUS/BEXUS programme. This German-Swedish student programme offers annual flights for student experiments on sounding rockets and stratospheric balloons. This paper gives a short overview on the development of the REXUS service system and points out the advantages of using standard interfaces for student experiments. Furthermore it contains a description of the REXUS-4 vehicle, the mission, the campaign and the experiments. Some experiments are described in more detail. During the ballistic flight the MIRIAM experiment of the University of Armed Forces in München and the Mars Society Germany was separated from the main payload to test a balloon system that will be used for the entry of a probe in the Martian atmosphere in the future. Several cameras on the REXUS-4 payload as well as cameras and telemetry on the MIRIAM flight system monitored the separation and inflation during the ballistic flight phase. The VERTICAL experiment from the Technical University München verified the start-up procedures of the CubeSat MOVE and its solar panel deployment under real ...